Proteomics profiling of inflammatory responses to elexacaftor/tezacaftor/ivacaftor in cystic fibrosis - Ozuna, Hazel; Bojja, Dinesh; Partida-Sanchez, Santiago; Hall-Stoodley, Luanne; Amer, Amal; Britt, Rodney D.; Sheikh, Shahid; Frank, David A.; Wang, Weiyuan; Kang, Bum-Yong; Miralda, Irina; Durfey, Samantha L.; et al. (Frontiers in Immunology, 2025)
BackgroundCFTR modulator therapies have positive clinical outcomes, yet chronic inflammation and bacterial infections persist in people with CF (pwCF). How elexacaftor–tezacaftor–ivacaftor (ETI) fails to improve innate immune signaling responsible for bacterial clearance and inflammation resolution remains unknown.MethodsWe used an unbiased proteomics approach to measure the effect of ETI on inflammatory proteins. Plasma from 20 pediatric pwCF and 20 non-CF (NCF) was collected during routine examination and 3 months after ETI initiation. Protein screening was performed with an inflammation panel (Target 96, Olink®). Bioinformatics analysis was used to determine changes in protein expression.ResultsThere were significantly fewer pulmonary exacerbations after ETI initiation, along with sustained improvement in lung function and reduced bacterial colonization. Unpaired analysis of CF pre-ETI and NCF resulted in 34 significantly different proteins. Of these, CCL20, MMP-10, EN-RAGE, and AXIN1 had a log2 fold change of 1.2 or more. There was a modest shift in overall CF protein profiles post-ETI toward the NCF cluster. Unpaired analysis of protein differential expression between NCF and CF post-ETI identified a total of 24 proteins significantly impacted by ETI therapy (p-value ≤ 0.05), with only CCL20 having a log2 fold change higher than 1.2. Paired analysis (CF pre- and CF post-ETI) of differential protein expression demonstrated significant expression changes of MMP-10, EN-RAGE, and IL-17A. Pathway analysis identified significantly impacted pathways such as the NF-κB pathway.ConclusionThis study showed that ETI in a pediatric cohort had a modest effect on several inflammatory proteins with potential as biomarkers. Pathways significantly impacted by ETI can be further studied for future therapies to combat persistent inflammation and dysregulated immunity.